Measurement of the electric field distribution in streamer discharges - Yihao Guo; Anne Limburg; Jesse Laarman; Jannis Teunissen; Sander Nijdam (Physical Review Research)
Using electric field induced second harmonic generation (E-FISH), we performed direction-resolved absolute electric field measurements on single-channel streamer discharges in 70 mbar (7 kPa) air with 0.2 mm and 2 ns resolutions. In order to obtain the absolute (local) electric field, we developed a deconvolution method taking into account the phase variations of E-FISH. The acquired field distribution shows good agreement with the simulation results under the same conditions, in direction, magnitude, and shape. This is the first time that E-FISH is applied to streamers of this size (>0.5 cm radius), crossing a large gap. Achieving these high resolution electric field measurements benefits further understanding of streamer discharges and enables future use of E-FISH on cylindrically symmetric (transient) electric field distributions.